An Examination of Market Efficiency in British Racetrack Betting - Gabriel, Paul E.; Marsden, James R. (Journal of Political Economy, 1990)
The nature of the British racetrack betting market provides a distinctly different opportunity for testing market efficiency. On the basis of data from a single racing season, we compare the returns to two similar forms of betting: (1) starting price bets placed with bookmarkers and (2) pari-mutuel tote bets. Our analysis indicates that tote returns are consistently higher than starting price returns, even though both betting forms are of similar risk and the payoffs are widely reported. The persistently higher tote returns suggest that the British racetrack betting market does not satisfy the conditions of semistrong efficiency. Our results also provide indirect support that the market fails to meet the conditions for strong efficiency.